2017
DOI: 10.1016/j.freeradbiomed.2017.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipid oxidation and carotenoid supplementation in Alzheimer’s disease patients

Abstract: Alzheimer's disease (AD) is a progressive, neurodegenerative disease, characterised by decline of memory, cognitive function and changes in behaviour. Generic markers of lipid peroxidation are increased in AD and reactive oxygen species have been suggested to be involved in the aetiology of cognitive decline. Carotenoids are depleted in AD serum, therefore we have compared serum lipid oxidation between AD and age-matched control subjects before and after carotenoid supplementation. The novel oxidised phospholi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 42 publications
1
34
0
Order By: Relevance
“…The excessive intake of vitamin A in the body causes poisoning, and b-carotene is a safe source of vitamin A because it can be converted to vitamin A after entering the body when needed. Studies have shown that b-carotene significantly improves behavioral abilities, learning, memory, and cognitive function in mice and rats through its antioxidant effect by scavenging free radicals (3,457).…”
Section: Fig 10mentioning
confidence: 99%
“…The excessive intake of vitamin A in the body causes poisoning, and b-carotene is a safe source of vitamin A because it can be converted to vitamin A after entering the body when needed. Studies have shown that b-carotene significantly improves behavioral abilities, learning, memory, and cognitive function in mice and rats through its antioxidant effect by scavenging free radicals (3,457).…”
Section: Fig 10mentioning
confidence: 99%
“…Our own work has shown that lutein, lycopene, and zeaxanthin concentrations were significantly lower in AD patients with vascular co-morbidities compared to healthy subjects [18]. In another study we have shown that the serum phospholipid oxidation product POVPC was higher in AD compared with age-matched control subjects but was not reduced by carotenoid supplementation in extant disease [19]. Taken together these studies indicate an inverse relationship between carotenoid concentration and the oxidised phospholipid POVPC in AD.…”
Section: Introductionmentioning
confidence: 68%
“…Glycerophospholipids, which are the most common phospholipids in vivo, comprise PC, PE, phosphatidylserine (PS), phosphatidylglycerol (PG), and phosphatidylinositol (PI). It was known that patients with AD have higher serum levels of PC, indicating that elevated PC may contribute to cognitive impairment (Ademowo et al, 2017), and higher brain levels of PC may lead to the impairment of the brain synapses. The elevated PC causes a decrease in acetylcholine release, which affects synaptic plasticity (Ulus et al, 1989;Wurtman, 2015).…”
Section: Discussionmentioning
confidence: 99%